2011
DOI: 10.4028/www.scientific.net/amr.264-265.1287
|View full text |Cite
|
Sign up to set email alerts
|

Laser Surface Melting of Austenitic Cr-Ni Stainless Steel

Abstract: The present paper deals with the microstructure and hardness distribution in width and in depth of the surface layer of steel Ch18N10T GOST (AISI 321, EN X6CrNiTi 18-10) after surface melting by continuous wave CO2 laser. Light microscopy, XRD analysis and Vickers hardness testing (HV5 and HV0,05) have been used in our research. Phase analysis shows disturbance of the mono-phase initial austenitic structure in the treated layer. The structure of the melted pool consists of austenite with dendrite morphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In some cases, successive etching processes take place. After laser melting during welding and heat treatment processes, the melted zone of the austenitic steel is characterized by a specific fine-grained microstructure formed as a result of the high heating and cooling rates (6). This causes additional difficulties when the microstructures of the molten zone and the base metal have to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, successive etching processes take place. After laser melting during welding and heat treatment processes, the melted zone of the austenitic steel is characterized by a specific fine-grained microstructure formed as a result of the high heating and cooling rates (6). This causes additional difficulties when the microstructures of the molten zone and the base metal have to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research studies were carried out to examine laser treatment of superalloy surfaces. Laser surface melting of austenitic Cr–Ni stainless steel was examined by Staurev et al Their findings revealed that in the melt pool, austenite with dendrite morphology and δ‐ferrite situated in the dendrite core were occurred. The grain refinement of austenitic stainless steel via laser heating was carried out by Yamoguchi et al They showed that fine ferrites were formed in the laser irradiated region, and the grain size on the average of 19 µm–15μm was resulted.…”
Section: Introductionmentioning
confidence: 99%